Sistem Keamanan Sepeda Motor Integerasi Sidik Jari dan Pelacakan GPS Tracker dengan Kontrol Jarak Jauh Berbasis ESP 32 di Sepeda Motor - Mukhlison Mukhlison; Andiko Dodik Nurjaya (Pusat riset dan Inovasi Nasional, 2025)
The high rate of motorcycle theft in Indonesia is a serious issue requiring an innovative, technology-based solution. This study aims to design and develop a motorcycle security system that integrates biometric authentication using a fingerprint sensor, real-time GPS tracking, and remote control based on the ESP32 microcontroller. The system allows users to start or stop the engine using registered fingerprints only, monitor vehicle location via GPS Tracker EV02, and control the motorcycle remotely through an internet-based application. Test results show that the system can accurately recognize fingerprints within 2 seconds, activate a buzzer for one minute upon unauthorized access attempts, and display the vehicle's location with an accuracy of 3–12 meters. Additionally, the use of the waterproof R503 fingerprint sensor ensures the system functions reliably in wet conditions. This integrated system has proven effective in enhancing the security of two-wheeled vehicles and offers a viable alternative to traditional security mechanisms.